Impacts of Sales Expense and Administrative Cost Stickiness on Earnings Management – Empirical Evidence from Vietnam - Hong Nguyen Thi Phuong; Thao Nguyen Thi Vo (Management)
This study aims to examine effects of sales cost stickiness and administrative cost stickiness on earnings management level. Next, the authors explore whether financial leverage, company size audit firm type and operating cash flow affect the earnings management level of Vietnamese stock exchanges listed companies. The research sample consists of 249 observations (83 companies excluding companies in the banking, finance and insurance sectors) taken from two Vietnamese stock exchanges, HNX and HOSE. For data analysis we use feasible generalized least square regression method. The research results find that sales expense stickiness and administrative cost stickiness, included in the model, have an impact on earnings management level. Sales cost stickiness has a positive impact, while administrative cost stickiness has an impact (negative) on earnings management level. Besides, operating cash flow has an impact on earnings management level, while company size, financial leverage and audit firm type found out with no effect on earnings management level. The results of the study contribute to helping investors, creditors or others have a more comprehensive view of profits and business results of companies so that they will be able to make rational decisions.